CuFe electrocatalyst for hydrogen evolution reaction in alkaline electrolysis. (19th October 2021) - Bhavanari, Mallikarjun; Lee, Kan-Rong; Tseng, Chung-Jen; Tang, I-Hsuan; Chen, Hao-Hsuan
Abstract: The development of high performance, stable catalyst with non-precious metals for electrochemical hydrogen evolution reaction for alkaline electrolysis is in demand. Here-in, we report the synthesis of CuFe layered double hydroxide (LDH) electrocatalyst on nickel foam via facile hydrothermal method. In alkaline electrolysis with 1 M NaOH electrolyte, CuFe LDH as cathode requires an overpotential of 159 mV to generate current density of 10 mA cm −2 . Which is ca. 51 mV and 7 mV lower than NiFe LDH and NiRu LDH. CuFe LDH exhibits significant electrocatalytic activity for HER. The higher catalytic activity of CuFe LDH compared to NiFe LDH may be achieved with higher proton adsorption by Cu compared to Ni. Also, the efficient charge transfer with interconnected LDH layers, favourable three dimensional structure facilitating easy electrolyte transfer to the active sites and hydrogen gas diffusion. This work may help in developing low cost and efficient hydroxide catalyst. Highlights: CuFe layered double hydroxide is prepared by hydrothermal process. Synthesis of low cost and non-precious metal electrocatalyst for electrolysis. CuFe LDH/Ni electrocatalyst requires only 159 mV at 10 mA cm −2 in HER. Stable after 5 h chronopotentiometry test.